Major factors why Kuehne + Nagel Bangladesh LTD. loses local customers despite being the leading freight forwarder in the world? - Evan, Ikram Hasan (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.